Sufis & saints' bodies: mysticism, corporeality, & sacred power in Islam - Kugle, Scott Alan (Islamic civilization and Muslim networks, 2007)
Introduction -- Body enshrined: the bones of Mawlay Idrīs -- Body politicized: the belly of sayyida Āmina -- Body refined: the eyes of Muḥammad Ghawth -- Body enraptured: the lips of Shāh Ḥussayn -- Body revived: the heart of Ḥājji Imdādullah -- Conclusion: corporeality and sacred power in Islam